MECHANICAL, PHYSICAL AND CHEMICAL DAMAGE TO THE MUCOUS MEMBRANE OF THE ORAL CAVITY, CLINIC, DIAGNOSIS, TREATMENT AND PREVENTION - Sodikova Shoira Amriddinovna; Bobodavlatov Dilshod; Muxammadiev Mirabbos (Journal Park Publishing, 2024)
This article explores the multifaceted aspects of mechanical, physical, and chemical damage to the mucous membrane of the oral cavity, delving into the clinic, diagnosis, treatment, and prevention strategies associated with these challenges. The oral mucosa, a crucial barrier protecting the underlying tissues, is susceptible to various forms of damage, including trauma, abrasions, thermal injuries, and exposure to harmful substances. The article navigates through clinical manifestations of mucosal damage, detailing diagnostic approaches such as clinical examinations and imaging techniques. Treatment modalities, ranging from conservative measures to advanced interventions, are discussed alongside preventive strategies aimed at minimizing the risk of mucosal injuries. By comprehensively addressing these aspects, this article aims to contribute to a better understanding and management of mechanical, physical, and chemical damage to the oral mucous membrane for enhanced oral health outcomes.
Keywords: Mechanical, physical, chemical damage, mucous membrane, oral cavity, clinic, diagnosis, treatment, prevention, trauma, abrasions, thermal injuries, harmful substances, clinical manifestations, imaging techniques, conservative measures.